2001
DOI: 10.1142/s0217732301003711
|View full text |Cite
|
Sign up to set email alerts
|

Energy Distribution of a Charged Regular Black Hole

Abstract: We calculate the energy distribution of a charged regular black hole by using the energy-momentum complexes of Einstein and Møller.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 19 publications
(14 reference statements)
3
26
0
Order By: Relevance
“…In this approximation the total energy is independent of the constant η. Finally we notice that the result (41) agrees with that given before [33,37].…”
Section: The Energy Associated With Each Solutionsupporting
confidence: 91%
“…In this approximation the total energy is independent of the constant η. Finally we notice that the result (41) agrees with that given before [33,37].…”
Section: The Energy Associated With Each Solutionsupporting
confidence: 91%
“…At the same time Bondi [18] sustained that a nonlocalizable form of energy is not admissible in relativity so its location can in principle be found. Since then, numerous works on evaluating the energy distribution of several gravitational backgrounds have been completed employing the abandoned for a long time approach of energymomentum complexes [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38]. In 1996 Aguirregabiria, Chamorro and Virbhadra [39] showed that five different 2 energymomentum complexes yield the same energy distribution for any Kerr-Schild class metric.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the standard vacuum case, Salti looked at the viscous Kasner universe in teleparallel gravity [36] using the Einstein and Landau-Lifshitz formulations and found the total energy and momentum to be identically zero. Generalizing these findings to another anisotropic cosmology, Radinschi examined the energy-momentum of the Bianchi type VIO universe using a number of different measures, finding that all the components vanish [37].…”
Section: Introductionmentioning
confidence: 96%